Perceived Worries and Spirituality: A Mixed Methods Study of the Primary Caregiver Well-Being of Orphan and Vulnerable Children in Ethiopia - Aweke Tadesse; Jesse J. Helton; Kenan Li (MDPI AG, 2024)
This study investigates the well-being of primary caregivers responsible for orphaned and vulnerable children. Well-being is defined as overall wellness, happiness, and satisfaction. Through mixed methods case studies and purposive sampling, we analyzed data from the Ziway Food for the Hungry Ethiopia program in 2017. Our explanatory analytic approach highlighted issues including resource constraints, chronic illnesses, and community challenges faced by the respondents. Nonetheless, spiritual well-being emerged as a crucial factor for their coping mechanisms. The findings underscore that critical well-being deficiencies require immediate attention. Strategies should prioritize financial and emotional support, emphasizing community capital to enhance the well-being of primary caregivers.